enter image description here

At infinity, i took limits to be L. so L= sin (x+L)

then after integration i am left withL= 2 cosL. how to get value of L

  • $\begingroup$ Note that $$\sin(a+b)=\sin(a)\cos(b)+\sin(b)\cos(a)$$ And $$\cos(a+b)=\cos(a)\cos(b)-\sin(a)\sin(b)$$ $\endgroup$ – clathratus Feb 12 '19 at 17:44
  • $\begingroup$ yes that i know. i m left with I= 2cos I $\endgroup$ – maveric Feb 12 '19 at 17:57


Assuming $\lim\limits_{n\to\infty}f_n(x)=f(x)$ the functional equation for $f(x)$ reads: $$ f(x)=\sin(x+f(x)).\tag1 $$

Instead of trying to resolve the equation (1) wrt $f$ one can easily resolve it (taking into account multivaluedness of $\arcsin$ function) wrt $x$: $$ x=\begin{cases} X_1(f)\equiv\arcsin(f)-f,& 0\le x\le\frac\pi2-1\\ X_2(f)\equiv\pi-\arcsin(f)-f,& \frac\pi2-1\le x\le\pi \end{cases}.\tag2 $$ and compute the integral in question as $$ \int_0^\pi f(x)dx=\int_0^1[X_2(f)-X_1(f)] df=\int_0^1[\pi-2\arcsin(f)] df=\color{red}2. $$

Extended hint:

To justify the equation $(2)$ it is necessary that the function $f(x)$ consists of exactly two monotonic branches: one increasing from $0$ to $1$ followed by the other decreasing from $1$ to $0$. The properties of $f(x)$ follow immediately from the equation $(1)$, provided that $g(x)\equiv x+f(x)$ is a monotonic function mapping $[0,\pi]\mapsto[0,\pi]$, and this is easy to demonstrate rewriting the equation $(1)$ as: $$g(x)=x+\sin(g(x)).$$

Indeed, $g(0)=0$ and $g(\pi)=\pi$ are the only possible solutions of

$$g(0)=\sin(g(0)),\quad\text{and}\quad g(\pi)=\pi+\sin(g(\pi)),$$
respectively, and $$ g'(x)=1+\cos(g(x))g'(x)\Rightarrow g'(x)=\frac1{1-\cos(g(x))}>0. $$

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.